Предмет: Алгебра, автор: Ксюша5664

АЛГЕБРА,РЕШИТЕ УРАВНЕНИЕ,ПОЖАЛУЙСТА

Приложения:

Ответы

Автор ответа: Luluput
0
 frac{3}{x+2} - frac{2x-1}{x+1}= frac{2x+1}{x^2+3x+2}
 frac{3}{x+2} - frac{2x-1}{x+1}= frac{2x+1}{(x+2)(x+1)}
ОДЗ:
x+2 neq 0,     x neq -2
x+1 neq 0,     x neq -1
  frac{3(x+1)-(2x-1)(x+2)}{(x+2)(x+1)} = frac{2x+1}{(x+2)(x+1)}
 frac{3x+3-(2x^2+4x-x-2)}{(x+2)(x+1)} = frac{2x+1}{(x+2)(x+1)}
 frac{3x+3-2x^2-3x+2}{(x+2)(x+1)} = frac{2x+1}{(x+2)(x+1)}   
 {3x+3-2x^2-3x+2} ={2x+1}
-2x^2+5} -2x-1}=0
-2x^2-2x+4=0
 x^{2} +x-2=0
D=1^2-4*1*(-2)=9
x_1= frac{-1+3}{2}=1
x_2= frac{-1-3}{2}=-2 - не удовлетв. 

Ответ: 1
Похожие вопросы
Предмет: История, автор: basovden0
Предмет: Алгебра, автор: Nat7355